PORTOFOLIO OPTIMAL SAHAM SYARIAH BUMN DENGAN INDEKS TUNGGAL - Sunaryono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study aims to identify sharia stocks of state-owned companies included in the IDX-MES BUMN17 sharia index to form an optimal portfolio and to determine the proportion of selected sharia stocks of state-owned companies from April 2021 to May 2023. This study also presents the return and risk levels of all IDX-MES BUMN17 stocks and the return and risk levels of the portfolio generated using the single index method. The analysis technique used is descriptive analysis using secondary data from 17 IDX-MES BUMN17 issuers obtained from www.idx.co.id, www.finance-yahoo.com, and www.bi.go.id. The population of this study consists of 17 stocks, and the entire population is used as the research sample. Based on the analysis results, two stocks were selected to form an optimal portfolio calculated since the establishment of the IDX-MES BUMN17 in April 2021, with an optimal assessment based on the ci value, namely PTBA and TLKM, with the largest proportion on the TLKM stock (30.01%) and PTBA (12.84%). The portfolio generated from these two stocks resulted in a return of 1.88% with a risk level of 8.75%.